(untitled) (Research, Society and Development, 2022)
Introduction: The treatment for obesity has shown great evolution in recent years. Liraglutide and semaglutide are drugs that act on weight loss, contributing to avoid the metabolic consequences that overweight can cause. As with all drugs, both have side effects, which influence treatment adherence. Objective: To search the literature for adverse reactions of semaglutide compared to liraglutide when used for weight loss. Methodology: The Cochrane Library, PubMED, LILACS, and CAPES databases were searched using the following keywords: "GLP-1", "adverse effects", "safety", "weight loss", "liraglutide", and "obesity", selecting articles in English and Portuguese published in the last 5 years. Reviews, meta-analyses, monographs, dissertation theses, books, incomplete articles, and studies whose population sample consisted of diabetics or that evaded the theme were excluded. Results: A final sample of 12 articles was selected. The main side effects in users of GLP-1 analogues were concentrated in the gastrointestinal system, namely nausea, vomiting, dyspepsia, constipation, diarrhea, and abdominal pain. Other systems also showed side symptoms, although at a lower frequency, such as central nervous system, cardiovascular, renal, and hepatic, as well as psychiatric events. The vast majority of the studies were conducted in adult participants, with only 1 in a sample of children. Few cases were classified as severe, with most symptoms being mild or moderate. Final Considerations: The use of semaglutide seems to be linked to side effects, especially in the gastrointestinal tract, of greater intensity when compared to liraglutide. However, weight loss was shown to be greater in semaglutide users.